The mechanisms of sensory habituation - Bagdonas , A. (Psichologija, 1972)
Up till now the existence of the special form of sensory habituation described by Hernandez Peon is an open question. The decrement of sensory reactions during repeated stimulation can be explained by the extinction of the sensory component of the orientation reaction. On the basis of literary data and his own experimental material the author confirms the latter explanation. In the paper a short analysis of views on the reasons of the dynamics of sensory reactions and a short summary of personal investigations is presented. The following data were used when creating the model of the extinction of the orientation reaction: l) the effect of specific stimulus includes two components: specific and non-specific; 2) repeating the specific stimulus the partial changes of sensory reactions (a partial habituation, a partial augmentation) are observed, which manifest themselves in the fact that quantitative parameters of sensory reactions change up to a certain level at which they remain with further stimulation; 3) nonspecific stimuli evoke fully extinctive reactions; 4) the character and parameters of partial and full habituation of sensory neurons correspond to the extinction character and parameters of the orientation reaction components or the reactions of non-specific neurons. On the basis of these facts one can assume that the extinction of the orientation reaction and its sensory component is the formation of a special inhibitory conditioned reflex. The repeated signal acting as a conditioned stimulus evokes the reaction of the inhibitory system. The latter blocks the activating reticular formation. The activating system prevails at the beginning of stimulation. During the stimulation the connection between the specific and inhibitory systems is formed. This temporary connection becomes stronger simultaneously with the augmentation of the inhibitory system's activity. An extra-stimulus or a change of the parameters of the stimulus disturbs the balance in favour of the activating system: the dishabituation phenomenon is observed. Thus the presented model accounts for the partial habituation of specific neurons and for the full habituation of non-specific neurons. The motivation system blocks the inhibitory system and takes part in the positive conditioning.
Keywords: habituation; sensing; sensory system